Conjugation of Peptide Nucleic Acid with a Pyrrole/Imidazole Polyamide to Specifically Recognize and Cleave DNA1. Issue 51 (23rd October 2013) - Kameshima, Wataru; Ishizuka, Takumi; Minoshima, Masafumi; Yamamoto, Makoto; Sugiyama, Hiroshi; Xu, Yan; Komiyama, Makoto
<x xml:space="preserve">Abstract</x> Cut loose: A pseudocomplementary peptide nucleic acid was tethered to a pyrrole/imidazole hairpin polyamide, and was used to selectively target a specific DNA sequence. Binding even occurs under high salt conditions. Furthermore, the conjugate facilitated sequence‐specific scission of long dsDNA. This simple approach promises to resolve the technical difficulties in targeting DNA sequences with PNA.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>